Biology and management of bark eating caterpillar, Indarbela quadrinotata in pomegranate - Satyanarayana, C; Arunakumaraskchitral@rediffmail.comskchitral@rediffmail.com, K T (Indian Journal of Plant Protection, 2020)
Biology of bark eating caterpillar, Indarbela quadrinotata Walker was studied in pomegranate during the year 2013-14. Eggs were 0.63 to 0.68 mm long and 0.38 to 0.43 mm wide. Eggs hatched in 6 to 9 days. Full grown larvae were 33 to 38 mm long and 4 to 6 mm wide. Larval duration was 271 to 294 days. Pupae were 9 to 12 mm long and 3 to 4 mm wide and the pupal period was 19 to 24 days. Male adult had a wing span of 9 to 11 mm length and width of 18 to 21 mm and lived for 4 to 5 days. Female adult had a wing span of 10 to 12 mm and width of 23 to 25 mm and lived for 4 to 5 days. Among the 8 chemicals evaluated, chlorantraniliprole 18.5 SC registered complete control of the pest and resulted in highest yield (10.12 t/ha and 10.07 t/ha during 2014 and 2015, respectively).